Beginning Excel 2019 - Brown, Noreen; Lave, Barbara; Romey, Julie (Open textbook library., 2019)
This textbook was written for a community college introductory course in spreadsheets utilizing Microsoft Excel. While the figures shown utilize Excel 2019, the textbook was written to be applicable to other versions of Excel as well. The book introduces new users to the basics of spreadsheets and is appropriate for students in any major who have not used Excel before. This textbook includes instructions for Excel for Mac also.